2008
DOI: 10.1063/1.2928637
|View full text |Cite
|
Sign up to set email alerts
|

Rotationally resolved electronic spectroscopy of water clusters of 7-azaindole

Abstract: Electronically excited states of water clusters of 7-azaindole: Structures, relative energies, and electronic nature of the excited states J. Chem. Phys. 128, 214310 (2008) The rotationally resolved electronic spectra of the electronic origin of the 7-azaindole-͑H 2 O͒ 1 and of the 7-azaindole-͑H 2 O͒ 2 clusters have been measured in a molecular beam. From the rotational constants the structures in the S 0 and S 1 electronic states were determined as cyclic with the pyrrolo NH and the pyridino N atoms being br… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
14
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 24 publications
4
14
0
Order By: Relevance
“…15 The present publication attempts to explain the experimental findings in a parallel experimental study on the excited states of the n = 1 and 2 water clusters of 7-azaindole. These results are presented in the accompanying study by Vu et al 16…”
Section: Introductionsupporting
confidence: 58%
See 1 more Smart Citation
“…15 The present publication attempts to explain the experimental findings in a parallel experimental study on the excited states of the n = 1 and 2 water clusters of 7-azaindole. These results are presented in the accompanying study by Vu et al 16…”
Section: Introductionsupporting
confidence: 58%
“…The values in parentheses give the experimentally determined rotational constants from Ref 13. for the monomer and from Ref 16. for the n = 1 and 2 water clusters.…”
mentioning
confidence: 99%
“…Some molecular systems change the energetic order of the excited states already upon addition of the first water molecules to the chromophore like azaindole. 3 Indole, as the chromophore of the aromatic amino acid tryptophane, has been extensively studied, mainly regarding the location of the higher electronically excited 1 L a state relative to the lowest 1 L b state, both experimentally [4][5][6][7][8][9][10][11][12] as well as theoretically. [13][14][15][16][17][18] Exchange of one hydrogen atom in the chromophore for the highly polar cyano group, changes the fluorescence properties of the indole chromophore considerably.…”
Section: Introductionmentioning
confidence: 99%
“…It could be shown that the lowest excited singlet state has 1 L b character, while the excitation in the n = 1 and n = 2 water clusters is to the 1 L a state. 3 Ahn et al 26 investigated 3-cyanoindole and several 3-cyanoindolewater clusters, using mass-selected resonant two-photon ionization (R2PI) and UV-UV hole-burning (UVHB) spectroscopy. Assignments of the different cluster structures were made on the basis of a Franck-Condon analysis of the vibronic spectra.…”
Section: Introductionmentioning
confidence: 99%
“…A well-known example is 7-azaindole (7AI, Figure 1), which forms doubly hydrogen bonded dimers in solution [2], while the X-ray data reveal a tetrameric structure in the crystalline state [3]. Different stoichiometries and structures are possible for the complexes of 7AI with methanol and water: 1 : 1, 1 : 2, and 1 : 3 species have been detected [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%